A new NAD+-dependent glyceraldehyde dehydrogenase obtained by rational design of l-lactaldehyde dehydrogenase from Escherichia coli. Issue 12 (1st December 2016) - Wu, Xing; Xu, Lin; Yan, Ming
Abstract: NAD + -dependent glyceraldehyde dehydrogenases usually had lower activity in the nonphosphorylated Entner–Doudoroff (nED) pathway. In the present study, a new NAD + -dependent glyceraldehyde dehydrogenase was engineered from l -lactaldehyde dehydrogenase of E. coli (EC: 1.2.1.22). Through comparison of the sequence alignment and the active center model, we found that a residue N286 of l -lactaldehyde dehydrogenase contributed an important structure role to substrate identification. By free energy calculation, three mutations (N286E, N286H, N286T) were chosen to investigate the change of substrate specificity of the enzyme. All mutants were able to oxidate glyceraldehyde. Especially, N286T showed the highest activity of 1.1U/mg, which was 5-fold higher than the reported NAD + -dependent glyceraldehyde dehydrogenases, and 70% activity was retained at 55 °C after an hour. Compared to l -lactaldehyde, N286T had a one-third lower K m value to glyceraldehyde. Graphical abstract: : Molecular structure of l -lactaldehyde dehydrogenase from E. coli.